PEMBERDAYAAN TENAGA KERJA DALAM MEMPRODUKSI JAMUR GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA KERU - Nurrahman, Nurrahman; Nurfaidah, Nurfaidah; Adawiyah, Hafizah Sa’datul; Mutmainnah, Mutmainnah; Endang , Hety Kus; Marlina, Marlina; Harman , Muafira; Sholehatun , Syaputri; Sasmita , Yuda Wisnu (Universitas Mataram, 2023)
Real Work Lecture (KKN) is a community service activity that is expected to be part of empowerment and learning for students to see the true social reality of society. In this activity, students are required to interact and try to solve various problems that exist in society and look for potentials that can be explored or utilized so that they can become sustainable activities, especially for environmental empowerment socialization activities, healthy environment, business, literacy both from the level of children, youth, and the elderly who are still illiterate or indifferent to science and other activities that can support village progress. With various problems that exist in the village, it is one of the reasons students take part and play an important role in village development. With the knowledge and experience gained in the campus environment, it becomes an asset for students to be present in the midst of the community providing education, space and cooperation to jointly develop the village. As is the case in the village of Keru, kec. Narmada is the venue for the 2022/2023 KKN class. Therefore, the Integrated KKN program will be carried out on December 19, 2022 in Keru Village, Kec. Narmada, West Lombok Regency. In Keru village, there are many potentials, one of which is the potential for natural products in the form of mushroom farming. However, the problem lies in the utilization of these agricultural products which are only sold raw, without being reprocessed into a product that has a high selling value. The method used in this study is an experimental method with various stages of activity, namely; 1. Planning, 2. Preparation, 3. Implementation, and 4. Results. From the results of implementing the KKN (Real Work Lecture) activities, it is possible to form a sustainable independent business, especially for housewives and form millennial business people. It is hoped that this kind of activity can continue and develop into a large-scale business.